Occupational and domestic physical activity and diabetes risk in adults: Results from a long-term follow-up cohort - Wang, Jialu; He, Liyun; Yang, Na; Li, Ziyi; Xu, Lingling; Li, Wei; Ping, Fan; Zhang, Huabing; Li, Yuxiu (Frontiers in Endocrinology, 2022)
Background: Physical activity (PA) has been associated with decreased incidence of diabetes. However, few studies have evaluated the influence of occupational and domestic PA on the risk of diabetes with a long-term follow-up. We aimed to examine the association between occupational and domestic PA and the risk of diabetes in a long-term prospective cohort of Chinese adults. Methods: A total of 10,343 adults who were followed up in the China Health and Nutrition Survey from 1997 to 2015 were included in our analysis. Occupational and domestical PA were collected with detailed seven-day data and were converted into metabolic equivalents values. Total PA included occupational, domestic, transportation, and leisure time PA. Diabetes cases were identified by self-reported doctor/health professional diagnosis of diabetes, fasting blood glucose ≥7.0 mmol/L, and glycosylated hemoglobin (HbA1c) ≥6.5%. Cox proportional hazards models were used to calculate hazard ratios (HR) and 95% confidence intervals (CI). Results: During up to 18 years of follow-up (median 10 years), there were 575 diabetes cases documented. Occupational PA accounted for the majority of total PA (68%) in Chinese population, followed by domestic PA (25%). With adjustments for possible covariates, the highest quartiles of total PA (HR, 0.728 [95% CI, 0.570–0.929]) and occupational PA (HR, 0.765 [95% CI, 0.596–0.982]) were significantly associated with a lower risk of diabetes compared with lowest quartiles. The association between domestic PA and the risk of diabetes was insignificant (P >0.05). Conclusion: Higher levels of occupational PA were associated with a decreased risk of diabetes risk in the Chinese population. Domestic PA was not associated with the incidence of diabetes.